1982
DOI: 10.1177/000306518203000106
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Studying the Analysis of Aspects of the Patients Experience of the Relationship in Psychoanalysis and Psychotherapy

Abstract: We have described a coding scheme for obtaining an objective account of the analysis of resisted aspects of the patient's experience of the relationship with the therapist in single, audio-recorded sessions of psychoanalysis and psychotherapy. The focus is on what is often regarded as an important first step in the analysis of transference: the identification and exploration of the preconscious points of attachment of transference ideas in the here-and-now. Related to the scheme is the view that there is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
4

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 5 publications
0
71
0
4
Order By: Relevance
“…'Confrontation' is a misleading term here. The patient is often unaware of or very hesistant to reveal his feelings about the therapist [22], In brief therapy this central transference difficulty must be examined systematically from the start of therapy. Sachs [23] observed that failure to make necessary interventions in a flexible way, or too superficial interventions, was connected with uproductive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…'Confrontation' is a misleading term here. The patient is often unaware of or very hesistant to reveal his feelings about the therapist [22], In brief therapy this central transference difficulty must be examined systematically from the start of therapy. Sachs [23] observed that failure to make necessary interventions in a flexible way, or too superficial interventions, was connected with uproductive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These serve to provide evidence for the analysis that in turn, guides futuristic behavior and choice of new experiences (Gill & Hoffman, 1982;Hobbs, 1966). For example, if a child is learning about primary and secondary color combinations, he might see that his inquiry with colors can have intended and non-intended outcomes as some colors can be created by other groupings while combining others leads toward an undesired color mixture.…”
Section: Lewinmentioning
confidence: 99%
“…Thomä (1996) stellt bezüglich der auch von Brockman zitierten Arbeiten von Piper et al (1986) und Henry et al (1994 außerdem korrigierend fest, dass der klinische Praxis in diesen Fällen der veralterte Übertragungsbegriff im Sinne der falschen Verknüpfung zu Grunde lag. Implizit geht er davon aus, dass die klinischen Anwendung des neuen interaktionellen Übertragungskonzepts von Gill (1982) vermutlich zu günstigeren Therapieerfolgen geführt hätte.…”
Section: Befunde Der Psychotherapieforschungunclassified